PTU-182 Specialist Care Of In-patients With Non-variceal Upper Gastrointestinal Bleeding Is Associated With A Significant Shorter Length Of Stay – A Prospective Analysis. (9th June 2014) - Venkatachalapathy, SV; Bright, R; Chung-Faye, G; Dubois, P; Forgacs, I; Logan, RP; Hayee, B
Abstract : Introduction: Acute upper gastrointestinal bleeding (UGIB) is a common medical emergency that has a 10% mortality rate, 1 requiring specialist input and management. 2 We conducted a retrospective review last year which showed that the mean length of stay (days) was shorter in the GI group: 5.5 ± 5.7 vs 15.7 ± 20.8 (p = 0.02). 3 We conducted a prospective analysis to assess if the above results held true. Methods: A prospective review of case-notes (Electronic patient record-EPR) was conducted for all patients admitted to Kings College hospital with suspected UGIB between January and September 2013. Patients were divided as to whether they came immediately under the care of Gastroenterologists (GI) or general physicians (non-GI) after initial evaluation in the Acute Admission Unit. Patients were assigned on the basis of bed availability in a ward-based system. Statistical comparisons were made as appropriate with two tailed t-test or chi- squared test. Results: 138 patient episodes were reviewed of which 63 and 75 were treated by GI and Non-GI physicians. The two groups were broadly similar in their baseline characteristics. Mean length of stay (days) was significantly shorter in the GI group: 6.6 ± 5.6Vs 10.66 ± 11.3 (p = 0.006). Other comparators are shown in the table. Conclusion: The length of stay of patients with UGIB is significantly shorter when receiving specialist care. In line with previous reports, 4 we found that the incidence of UGIB was higher in males. Patients managed by GI physicians received less blood transfusion compared to the Non-GI physicians. The time to endoscopy was significantly shorter when receiving specialist care. Mortality rates in both groups compared favourably to the national average. References: CG141 Scope for improvement: A toolkit for a safer Upper Gastrointestinal Bleeding (UGIB) service. www.bsg.org.uk Venkatachalapathy SV, Grasso N, Hayee B et al., Specialist care of in-patients with non-variceal upper gastrointestinal bleeding is associated with a dramatically shorter length of stay. Gut 2013;62:A10 doi:10.1136 Lanas A, García-Rodríguez LA, Polo-Tomás M et al ., Am J Gastroenterol 2009;104:1633-41 Disclosure of Interest: None Declared.